Farmer Preferences for Organic Fertilizer Attributes: A Conjoint Analysis of Okiagaru Agricoop - Doni Sahat Tua Manalu; Andini Tribuana Tunggadewi; Agief Julio Pratama; Made Gayatri Anggarkasih; Abung Supama Wijaya (Universitas Panji Sakti, 2026)
The use of organic fertilizers in horticultural farming remains limited due to farmers’ perceptions regarding effectiveness, practicality, and economic considerations. Understanding farmers’ preferences for organic fertilizer attributes is therefore important to support the adoption of sustainable agricultural practices. This study aims to analyze the preferences of Okiagaru Agricoop partner farmers toward organic fertilizer attributes in horticultural cultivation in Cianjur Regency, West Java. This study employed a descriptive quantitative approach using conjoint analysis to evaluate farmers’ preferences for different combinations of fertilizer attributes. Data were collected through field observations, questionnaires, and direct interviews with 30 partner farmers selected using purposive sampling. The attributes analyzed included price, quality, effectiveness, and ease of use. The results show that ease of use is the most influential attribute, with the highest importance value (30.397%) and utility estimate (0.542), indicating that farmers strongly prefer fertilizers that are easy to apply in farming activities. This was followed by quality (23.580%), effectiveness (23.093%), and price (22.930%). In addition, most farmers (96.67%) expressed their willingness to process organic waste into organic fertilizer. These findings indicate that practical and functional attributes play a crucial role in farmers’ decisions to adopt organic fertilizers. Therefore, the development and dissemination of organic fertilizer technologies should prioritize ease of application, effectiveness, and affordability to encourage wider adoption among horticultural farmers.